SCHIZOPHRENIA AND ITS REPRESENTATIONS IN BRAZILIAN MUSIC: THE POETICS OF MADNESS - Rocha, Raquel (Health and Society, 2023)
This article proposes to investigate the meanings of madness and the crazy person in five songs that address the theme: Balada do Louco, Maluco Beleza, Hino dos Malucos, Bicho de sete cabezas and Sufoco da vida. The objective is to compare the literary discourses about the crazy and madness with the guidelines in the World Health Organization Report: Mental Health: new conception, new hope of 2001. The analysis of song lyrics allowed the association with the approach of different authors and with the report from the World Health Organization. The songs discuss important problems such as violence in asylum institutions, social medicalization and prejudice. The lyrics also refer to the issue of the patient’s capabilities and establish a fine line between madness and normality. More than corroborating with the perspectives of mental health, through this analysis it is believed that music can be a supporting agent in the process of social awareness as recommended by the World Health Organization. It is noteworthy that this discussion goes beyond the field of mental health also covering the field of culture, debating how society relates to the experience of madness and discussing its implications.